2014
DOI: 10.1177/1938965514535974
|View full text |Cite
|
Sign up to set email alerts
|

Inter-channel Effects in Multichannel Travel Services

Abstract: Travel agents continue to offer traditional services, but as customers migrate to online sales channels, many traditional agencies have added their own online distribution channels. This study of the attitudes of 114 university students finds that excellence in offline service is associated with a favorable view of an agent’s online presence. Moderating this relationship is the effect of social presence (SP) on the website. That is, the respondents’ view of the website was improved by the availability of live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…However, according to Gefen and Straub (2003), the integration of personalised, humancontact cues and synchronicity, may encourage the perception of a higher level of social presence. For instance, Aslanzadeh and Keating (2014) showed how the integration of video chat interactions into a travel provider's website enhances the perceived level of social presence and, as a result, affects consumers' channel preferences.…”
Section: Travel Service Computer-mediated Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, according to Gefen and Straub (2003), the integration of personalised, humancontact cues and synchronicity, may encourage the perception of a higher level of social presence. For instance, Aslanzadeh and Keating (2014) showed how the integration of video chat interactions into a travel provider's website enhances the perceived level of social presence and, as a result, affects consumers' channel preferences.…”
Section: Travel Service Computer-mediated Interactionsmentioning
confidence: 99%
“…This study offers several theoretical contributions. First, by building on previous research (e.g., Aslanzadeh and Keating, 2014;Kang et al, 2015;, the study presents the consequences of online human live chat communication and the intervening effects of human elements through the lens of social presence theory. In this sense, it offers a unique contribution to the travel literature by providing empirical insights and conceptual clarity into the usefulness of human operated live chat communication on travellers' attitudes, trust towards the website and purchase intentions.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the ease of connection with the company could increase the intention to have a direct relationship with a corporate customer care office, chatting or phoning with Skype. A recent study by Aslanzadeh and Keating (2014) found that live-chat and video-chat satisfy the need for human interaction during all the steps of the decision making process.…”
Section: Social Media Customer Carementioning
confidence: 99%
“…Following this question, participants were asked to answer seven questions about their continuance intentions (e.g. “I would make an effort to use the service provider”) (Aslanzadeh and Keating, 2014). All measures used 7-point Likert scales (1 = strongly disagree, 7 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%